Financial Management Capability Matters in Capabilities—Performance Relationships: The Case of Two Industries - Mehdi Younes Garrab (SAGE Open)
I proposed a model relying on a typology of four types of capabilities: operations, technological, financial management, and marketing capabilities. The empirical study used a panel of data collected on 89 automotive and 117 pharmaceutical companies. The capabilities are measured with the use of the Data Envelopment Analysis (DEA) method. Results showed that in both industries, financial management capabilities need enhancement to maintain a competitive position and ensure a higher level of performance. Also, managers need to emphasize marketing capabilities and tangible investments in the automotive industry and technological capabilities and intangible investments in the pharmaceutical one. Among contributions, I proposed a design and measure of financial management capability and used the DEA method for the estimation of capabilities, as done by previous studies.